DEVELOPMENT OF HUMAN FACTORS ANALYSIS & CLASSIFICATION SYSTEM (HFACS) METHOD AND ANDROID BASED APPLICATION FOR INVESTIGATING MEDICATION ERRORS ON HOSPITAL OUTPATIENT PHARMACY DEPARTMENT WORKERS - Sundara, Gilar
Human factors play an important role in various fields because human factors help analyze the relationship among three aspects: the individual at work, the tasks copied with, and the workplace itself. The health service sector needs to be highlighted in the development of human factors due to not only its occupational safety and health workers’ safety, but also patient safety. One of human factors incindent that causes errors in treatment involving health workers is medication errors. To overcome this, it is necessary to develop and manage a patient safety reporting system, analysis, and approval system of patients’ safety. Human Factor Analysis and Classification System (HFACS) is a method developed to investigate and analyze the factors that cause medication errors in outpatient pharmacists in hospitals. This research aims to: validate HFACS which has been adapted for investigating cases of medication errors in the outpatient pharmaceutical service system in hospitals; to develop Android-based mobile application that can facilitate the investigation and analysis of medication errors using HFACS; and to evaluate the usability of the mobile application that has been developed. This developed HFACS is named as HFACS-Pharm then enriched with its mobile application. HFACS-Pharm validation was carried out by observing 55 results of the assessment of 11 cases of medication errors that occurred during September 2019 at the Dr. Hasan Sadikin Bandung. Validator consisted of experts include pharmacist officers in hospital pharmacy installation and 17 pharmacy technician in outpatient pharmacy department. To ensure the validity, a reliability test was conducted. It was found that the total percentage agreement value of each pair of respondents per all cases was 71.87% and was included in the acceptable level. The development of its mobile application is done by completing the conceptual design and then making its prototype. The conceptual design was designed based on both the HFACS-Pharm questionnaire and the function of health workers in the hospital, related to the procedure of reporting errors in hospital outpatient pharmacy department. The application is made up to the clickable prototype following the predetermined conceptual design and then adapted to Android-based programming features. Usability testing of HFACS-Pharm mobile application is conducted using the retrospective think aloud method. A total of 10 new users participated. 3 of the participants were involved by remote testing method. Preliminary revision of the application is done after pilot testing. Then, the revised application was tested with several scenarios. The results obtained that the mobile application has reached the user-interface effectiveness level of 78%-80% and the average duration needed to complete the HFACS-Pharm questionnaire was 26.68 minutes. These results should be optimized by some recommendations and implementation upon real users.